L’Haïtianité et la responsabilité sociale de la diaspora dans le développement d’Haïti - Bénédique Paul; Hugues Séraphin (Études Caribéennes)
Haitian identity, namely Haitianity, is even stronger within the Haitian Diaspora than it is within Haitians stayed in the country. This Haitianity that appears like a social movement has contributed to help the Haitian Diaspora be inserted in host countries and become major player in the development of Haiti. The Diaspora is seen as an asset that should be used for the economic development of the country.